1997
DOI: 10.1111/j.1398-9995.1997.tb02603.x
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis simplex, a relevant etiologic factor in acute urticaria

Abstract: Anisakis simplex, a parasite of fish and cephalopods, can induce IgE-mediated reactions. This study aimed to determine the etiologic role of A. simplex in patients affected by urticaria/angioedema (AE) or anaphylaxis. We studied 100 adult subjects suffering acute episodes of urticaria/AE, by anamnesis, prick tests with A. simplex and fish-mix extracts, and total and specific IgE to both A. simplex and cod. The following criteria of A. simplex allergy were considered: 1) urticaria/AE within 6 h after fish inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(43 citation statements)
references
References 11 publications
1
39
0
3
Order By: Relevance
“…21,2008 ANISAKIS SIMPLEX PATHOGENESIS 363 appeared from the central region of Spain but were there associated with gastrointestinal anisakidosis and with raw anchovies in vinegar (69). Moreover, a significant number of fishmongers and fishermen in Italy and African fish-processing workers, as well as 13% of healthy blood donors, are sensitized to this parasite (82,201,221). It should be borne in mind, however, that specific immunoglobulin E (IgE) detection by ImmunoCAP assay can overestimate the number of sensitized subjects (165,167), so the above estimates may be exaggerated.…”
Section: Allergic Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,2008 ANISAKIS SIMPLEX PATHOGENESIS 363 appeared from the central region of Spain but were there associated with gastrointestinal anisakidosis and with raw anchovies in vinegar (69). Moreover, a significant number of fishmongers and fishermen in Italy and African fish-processing workers, as well as 13% of healthy blood donors, are sensitized to this parasite (82,201,221). It should be borne in mind, however, that specific immunoglobulin E (IgE) detection by ImmunoCAP assay can overestimate the number of sensitized subjects (165,167), so the above estimates may be exaggerated.…”
Section: Allergic Symptomsmentioning
confidence: 99%
“…In the allergic cases from this region, the consumption of cooked hake (Merluccius merluccius) predominates, closely followed by cooked or raw anchovies (29,95) (Table 1). It is becoming apparent that A. simplex is the most important hidden food allergen in the adult population suffering acute urticaria (82) and anaphylaxis (28,29) of the Basque Country in northern Spain, and this recognition has now spread to other regions in Spain (13). It is also the etiologic factor most commonly associated with urticaria for any specific food allergy in the adult population and comprises as much as 10% of the anaphylaxis previously diagnosed as idiopathic (28) (Fig.…”
Section: Allergic Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of acute gastric infection include sudden epigastric pain, nausea and vomiting and can occur 1–12 h after the infected meal [1]. Anisakiasis is often associated with a strong allergic response, with clinical symptoms ranging from isolated swelling to urticaria, angioedema and life-threatening anaphylactic shock [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients who develop allergic symptoms (urticaria/angioedema and anaphylaxis) after the ingestion of fish are frequently sensitized to allergens of this nematode [2, 6, 7, 8]. Occupational conjunctivitis [9]and asthma [10], supposedly induced by A. simplex , have also been reported.…”
Section: Introductionmentioning
confidence: 99%